2021
DOI: 10.1039/d1sc02575a
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective tandem iridium-catalyzed alkene isomerization-cope rearrangement of ω-diene epoxides: efficient access to acyclic 1,6-dicarbonyl compounds

Abstract: The Cope rearrangement of 2,3-divinyloxiranes, a rare example of epoxide C-C bond cleavage, results in 4,5-dihydrooxepines which are amenable to hydrolysis, furnishing 1,6-dicarbonyl compounds containing two contiguous stereocenters at the 3- and 4- positions. We employ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Marek's group used Ir-catalyzed Cope rearrangements to produce medium-sized ring structures through ring expansion reactions. In 2019, 7-memebered dienes were synthesized from alkenyl ω-ene cyclopropanes or epoxides 147 via Ir-catalyzed tandem olefin migration and Cope rearrangement (Scheme 30) [67,68]. Migration of the terminal olefin successfully occurred in the presence of a cationic Ir catalyst system to produce 1,5-dienes 148.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Marek's group used Ir-catalyzed Cope rearrangements to produce medium-sized ring structures through ring expansion reactions. In 2019, 7-memebered dienes were synthesized from alkenyl ω-ene cyclopropanes or epoxides 147 via Ir-catalyzed tandem olefin migration and Cope rearrangement (Scheme 30) [67,68]. Migration of the terminal olefin successfully occurred in the presence of a cationic Ir catalyst system to produce 1,5-dienes 148.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In the past decades, carbonyl metallic salts have been used as operatable homogeneous catalysts for carbonylation of epoxides. In fact, researchers have reported in detail on the ring expansion and ring-opening carbonylation of epoxides (Suresh et al, 2021). However, complicated homogeneous reaction systems were dominantly used with metastable metal carbonyls with unsatisfied product yields.…”
Section: Introductionmentioning
confidence: 99%
“…To challenge the two hypotheses presented above, our model substrate 1a (R = n -Pr), easily synthesized through the Ni-catalyzed hydroalumination-transmetalation sequence of alkynes developed by Hoveyda, 37 was first submitted to our slightly modified Ir-based isomerization conditions (see Supporting Information ). 35 , 47 49 …”
mentioning
confidence: 99%
“…During the course of our study, Huang and Guo et al have reported an elegant Fe–H-catalyzed isomerization resulting in trisubstituted ( Z )-alkenyl­boronates (Scheme f), leading us to disclose our results herein. For the formation of ( E )-alkenyl­boronates, our strategy relies on an Ir-based alkene isomerization catalyst operating through a 1,3-hydride shift mechanism. , In this mechanistic scenario, the key allyl iridium hydride intermediate prefers a “W-shaped” conformation where the substituents at the termini of the allylic system point away from the bulky iridium center ( A , Scheme a) rather than toward it ( B ). Reinsertion of the hydride would result in the formation of the E -alkenyl­boronate ester.…”
mentioning
confidence: 99%
See 1 more Smart Citation